A bifunctional dermaseptin–thanatin dipeptide functionalizes the crop surface for sustainable pest management. Issue 9 (1st April 2019) - Schwinges, Patrick; Pariyar, Shyam; Jakob, Felix; Rahimi, Mehran; Apitius, Lina; Hunsche, Mauricio; Schmitt, Lutz; Noga, Georg; Langenbach, Caspar; Schwaneberg, Ulrich; Conrath, Uwe
Abstract : A bifunctional dipeptide can help to reduce pesticide use while preserving crop productivity. Abstract : To reduce pesticide use while preserving crop productivity, alternative pest and disease control measures are needed. We thought of an alternative way of functionalizing leaves of soybean to fight its most severe disease, Asian soybean rust ( Phakopsora pachyrhizi ). To do so, we produced bifunctional peptides that adhere to the soybean leaf surface and prevent the germination of P. pachyrhizi spores. In detail, amphiphilic peptides liquid chromatography peak I (LCI), thanatin (THA), tachystatin A2 (TA2), and lactoferricin B (LFB) were all fused to enhanced green fluorescent protein (eGFP). Of these fusion peptides, eGFP–LCI and eGFP–THA bound strongly and in a rainfast manner to the surface of soybean, barley, and corn leaves. eGFP–THA binding to soybean also withstood high temperature, sunlight and biotic degradation for at least 17 days. The dipeptides seem to bind mainly to the surface wax layer of leaves because eGFP–THA and eGFP–LCI did not stick to the wax-depleted cer-j 59 mutant of barley or to corn leaves with their surface wax removed. A fusion of the antimicrobial peptide dermaseptin 01 and THA (DS01–THA) inhibits the germination of P. pachyrhizi spores in vitro and reduces Asian soybean rust disease in a rainfast manner. Therefore, this study reveals that bifunctional peptides can be used to functionalize the crop surface for sustainable disease management.